Characterization of a cohort of Angolan children with sickle cell anemia treated with hydroxyurea - Santos, Brígida (2024)
Background: Sickle Cell Anemia (SCA) is a monogenic disease, although its severity and response to treatment are very heterogeneous. Objectives: This study aims to characterize a cohort of Angolan children with SCA and evaluate their response to hydroxyurea (HU) treatment and the potential side effects and toxicity. Methods: The study enrolled 215 patients between 3 and 12 years old before and after the administration of HU, at a fix dose of 20 mg/kg/day for 12 months. Results: A total of 157 patients started HU medication and 141 of them completed the 12-month treatment. After initiating HU treatment, the frequency of clinical events decreased (transfusions 53.4 %, hospitalizations 47.1 %). The response to HU medication varied among patients, with some experiencing an increase in fetal hemoglobin (HbF) of <5 %. The mean increase in HbF was 11.9 %, ranging from 1.8 % to 31 %. Responders to HU treatment were 57 %, inadequate responders 38.7 % and non-adherent 4.2 %. No clinical side effects related to HU were reported. Hematological toxicities were transient and reversible. Children naïve to HU and with lower HbF reported higher number of hospitalizations caused by malaria infection. During HU treatment, the frequency of malaria episodes did not appear to be affected by HbF levels. Conclusions: the present study provided a valuable contribution to the understanding of the clinical and laboratory profiles of Angolan children with SCA. These findings support the evidence that the implementation of prophylactic measures and treatment with HU is associated with increased survival in children with SCA.